Structural characterization of polysaccharide from Centipeda minima and its hypoglycemic activity through alleviating insulin resistance of hepatic HepG2 cells. (July 2021) - Chen, Juncheng; Li, Lin; Zhang, Xia; Wan, Liting; Zheng, Qingsong; Xu, Dan; Li, Yuting; Liang, Yi; Chen, Meisi; Li, Bing; Chen, Zhiyi
Graphical abstract: Highlights: A homogeneous heteropolysaccharide was isolated and purified from Centipeda minima . The backbone chain of CMP-2B were 3, 6)-α-D-Man p -(1 and 4, 6)-β-D-Gal p -(1. CMP-2B possessed preferable antioxidant and α-glucosidase inhibitory activity. CMP-2B could improve insulin resistant in IR-HepG2 cells. Abstract: A novel polysaccharide (CMP-2B) was purified from Centipeda minima by anion-exchange and gel-permeation chromatography. Structural characterization revealed that CMP-2B was a homogeneous heteropolysaccharide with an average molecular weight of 113.193 KDa. CMP-2B was made up of mannose, galacturonic acid, galactose and arabinose with a molar ratio of 0.27:0.12:0.42:0.17. The backbone chain of CMP-2B consisted of 3, 6)-α-D-Man p -(1 and 4, 6)-β-D-Gal p -(1, and the branches were comprised of 4)-α-D-Gal p A-(1, 6)-β-D-Gal p -(1, T-α-L-Ara f -(1 and 3)-α-L-Ara f -(1. Besides, the results of antioxidant assays revealed that CMP-2B possessed signifcant free radical scavenging ability. Moreover, the results of hypoglycemic assays showed that CMP-2B displayed α-glucosidase inhibitory activities, and could significantly improve glucose consumption, glycogen synthesis and the activity of pyruvate kinase of insulin-resistance HepG2 cells. Overall, these results suggested that CMP-2B could be a new source for functional foods.